1975
DOI: 10.1111/j.1423-0410.1975.tb00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Abnormalities in the Sera of IgA‐Deficient Blood Donors

Abstract: Immunological abnormalities of 163 IgA-deficient blood donors were studied. Anti-IgA antibodies were found in 15, anti-IgG antibodies (measured by the Ripley test) in 34, latex test positivity in 21, anti-IgM antibodies in 9 and antibodies against bovine milk in 41 sera. These numbers differed significantly from the control groups of normal blood donors. In the studies of thyroglobulin antibodies, antinuclear antibodies and blood group A and B isoagglutinins there was no difference from the controls. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 18 publications
6
22
0
Order By: Relevance
“…Elevated levels of various autoantibodies, in the absence of associated clinical autoimmunity, have previously been observed in IgAD subjects [3,5,26,27]. Elevated serum levels of antithyroglobulin and antithyroid microsome antibodies have been observed in 10 -15% of IgAD subjects [5]; however, to our knowledge, this is the first time that serum TRAb levels have been evaluated in two different IgAD cohorts.…”
Section: Association Of Serum Iga and Igad With Serum Trab Levelsmentioning
confidence: 65%
See 2 more Smart Citations
“…Elevated levels of various autoantibodies, in the absence of associated clinical autoimmunity, have previously been observed in IgAD subjects [3,5,26,27]. Elevated serum levels of antithyroglobulin and antithyroid microsome antibodies have been observed in 10 -15% of IgAD subjects [5]; however, to our knowledge, this is the first time that serum TRAb levels have been evaluated in two different IgAD cohorts.…”
Section: Association Of Serum Iga and Igad With Serum Trab Levelsmentioning
confidence: 65%
“…Hence, the increase in multiple different autoantibodies reported in IgAD individuals might explain the difference between immunoassays [36,37]. Increased prevalence of rheumatoid factor has consistently been found within IgAD populations [5,27] and it is also known to interfere with immunoassays accountability by immunoglobulin aggregation [38]. In addition, it has been found to be falsely elevated in IgAD individuals [39].…”
Section: Association Of Serum Iga and Igad With Serum Trab Levelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Possibly the absence of functioning mucosal immunity plays a role in the immune complex disease. Even healthy IgA-deficient subjects have a defective gut absorption mechanism which allows foreign antigenic material to enter the circulation [7]. Van der Woude et al [8] showed the relationship between circulating immune complexes by food antigens and GN in a patient with IgA deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent Cassidy et al (1969Cassidy et al ( , 2007, Rankin and Isenberg (1997) with the increased prevalence of systemic AD in IgAD. The autoantibodies detected include rheumatoid factor, antinuclear antibodies, anti-DNA antibody, anti-single-stranded DNA antibodies, anti-RNA antibodies, and anticardiolipin antibodies (Koistinen and Sarna, 1975;Gershwin et al, 1976;Ammann et al, 1979;Funakoshi et al, 1985;Pascual-Salcedo at el., 1988;Goshen et al, 1989;Jimenz et al, 1991).…”
Section: Autoimmunitymentioning
confidence: 99%